Oral Administration of Extract from Curcuma longa Lowers Blood Glucose and Attenuates Alloxan-Induced Hyperlipidemia in Diabetic Rabbits - Nwozo, Sarah; Adaramoye, Oluwatosin; Ajaiyeoba, Edith (Pakistan Journal of Nutrition, 2009)
The biochemical effects of methanol extract of Curcuma longa on plasma cholesterol, glucose, protein, triglyceride and creatinine levels were studied in alloxan induced diabetic rabbits. The rabbits were induced by intra-peritoneal injection of alloxan, which was prepared in proportion to the rabbit’s body weight and administered per kilogram body weight of each rabbit. The animals were placed into three main groups in this study: normal, diabetic test animals and diabetic control animals. Single doses of plant extracts were used for the respective studies and the biochemical parameters were assessed from day 0 to day 12, on day 3 respectively. The results of plasma glucose levels indicated an increase from 6.6-8.0 g/L in the diabetic rabbits treated with C. longa extract, compared to the diabetic control which maintained a level of 6.3 g/L. Creatinine level in the test animals decreased from 264.5-94.6 μmol/L and plasma cholesterol in the test group. However the plant extract only showed a slight decrease in the plasma triglyceride and protein levels of alloxan diabetic rabbits. Polydipsia in untreated in diabetic animals was reduced to normal in those administered the plant extract. Curcuma longa could be a possible source of antidiabetic chemotherapeutic agents.